MENGINTEGRASIKAN TEKNOLOGI INFORMASI DAN GAME BASED LEARNING DALAM PAI: STUDI KUALITATIF TENTANG DESAIN, URGENSI, DAN DAMPAK ZEP QUIZ - Sabrina Syifaurrahmah; Fadhilah Izzah Khairunnisa; Karoma; Muhammad Isnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology demands a transformation in Islamic Religious Education (PAI), yet it faces challenges such as infrastructure inequality, limited digital learning materials, and low teacher digital literacy. This study aims to analyze adaptive learning strategies through the integration of Information Technology and Game-Based Learning (GBL) using Zep Quiz, as well as to describe its design, urgency, and impact. The research method employed is descriptive qualitative to elucidate the role of technology in PAI, supported by the 4D development model (Define, Design, Develop) in game design. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The results indicate that the integration of IT and GBL creates flexible (anytime, anywhere) and interactive learning environments. The development of Zep Quiz through the stages of defining, designing, and developing has proven to increase students' motivation, engagement, and understanding of PAI materials. Although challenges such as costs and distraction risks exist, solutions including teacher training, Islamic content validation, and multi-party collaboration are recommended. In conclusion, Zep Quiz-based GBL serves as an effective innovation for internalizing Islamic values contextually in the digital era.